Effect of Perceived E-Service Quality Towards Behavioral Intention Mediated by Customer Satisfaction: A Case of UNIQLO Indonesia - Daniellus Wilfredo (iBuss Management, 2023)
This study investigates the connection between online repurchase intent and perceived e-service quality in the context of UNIQLO Indonesia. This study's goal is to analyze how perceived e-service quality affects behavioral intentions and the mediating function that customer satisfaction plays in this relationship. The PLS-SEM method was used to conduct the study among 356 valid respondents where the respondents are UNIQLO consumers in Indonesia. The study utilizes probability sampling where the sampling method used is simple random sampling. The study received responses from the respondents through an online questionnaire that was shared through several social platforms. The results of this study shed light on how perceived e-Service quality affects behavioral intention as well as the mediating role that customer satisfaction plays. The findings show that perceived e-service quality significantly affects behavioral intention, highlighting its significance for UNIQLO Indonesia's online success. The study also demonstrates that customer satisfaction partially mediates the association between perceived e-service quality and behavioral intention, underscoring the relationship's importance.Keywords: Perceived e-service quality, Customer satisfaction, Behavioral intention, UNIQLO Indonesia.